Relationship Between Brain Glutamate Levels and Clinical Outcome in Individuals at Ultra High Risk of Psychosis - Egerton, Alice (Nature Publishing Group, 2014)
Alterations in brain glutamate levels may be associated with psychosis risk, but the relationship to clinical outcome in at-risk individuals is unknown. Glutamate concentration was measured in the left thalamus and anterior cingulate cortex (ACC) using 3-Tesla proton magnetic resonance spectroscopy in 75 participants at ultra high risk (UHR) of psychosis and 56 healthy controls. The severity of attenuated positive symptoms and overall functioning were assessed. Measures were repeated in 51 UHR and 33 Control subjects after a mean of 18 months. UHR subjects were allocated to either remission (no longer meeting UHR criteria) or non-remission (meeting UHR or psychosis criteria) status on follow-up assessment. Thalamic glutamate levels at presentation were lower in the UHR non-remission (N=29) compared with the remission group (N=22) (t(49)=3.03; P=0.004), and were associated with an increase in the severity of total positive symptoms over time (r=−0.33; df=47; P=0.02), most notably abnormal thought content (r=−0.442; df=47; P=0.003). In the UHR group, ACC glutamate levels were lower at follow-up compared with baseline (F(80)=4.28; P=0.04). These findings suggest that measures of brain glutamate function may be useful as predictors of clinical outcome in individuals at high risk of psychosis.